Emotional intelligence of medical undergraduates: a cross sectional study - Ukey, Ujwala U.; Sharma, Sarita K.; Rathod, Pragati; Patil, Sonali S.; Choudhary, Sanjeev M.; Narlawar, Uday (International Journal Of Community Medicine And Public Health, 2019)
Background: Emotional intelligence (EI) is defined as the ability to perceive, access and generate emotions. This in turn will assist thoughts to understand emotions and emotional meanings and thus reflectively regulate emotions so as to promote both better emotional and intellectual growth. EI is essential for a competent physician. The present study was conducted to know the EI of medical students. Methods: A cross sectional study was conducted at Government Medical College Nagpur among final year part 1 medical undergraduates. Data was collected with the help of pre tested, predesigned, self-administered proforma based on the “quick emotional intelligence self-assessment questionnaire”. Statistical analysis was done with epi info software and appropriate statistical tests were applied to prove the significance. Results: Of the total 197 study participants, 100 (50.76%) were female students and remaining 97 (49.24%) were male students. Mean score for EI was 102.16 With 95% confidence the population mean is between 99.6 and 105. Conclusions: Emotional intelligence for most of the study participants belonged to ‘consider strengthening’ category indicating good scores. Female medical undergraduates were more emotionally intelligent than male students.